Orthodontic treatment in patients with reduced periodontal insertion - Fernanda Labayle Couhat Carraro; Cristina Jimenez-Pellegrin (Faculdade São Leopoldo Mandic, 2009)
The aim of this study was to conduct a literature review to investigate orthodontic treatment in periodontal patients. Periodontal disease causes loss of attachment that results in pathological dental migration Periodontal disease can affect young persons and adults, with a higher incidence in adults, so that the number of adults seeking orthodontic treatment has increased significantly. The periodontal disease must be controlled before the orthodontic treatment begins, and during the treatment it is important to keep the patient motivated as regards control of oral hygiene, with periodical reviews by the periodontist. With regard to assembly of the fixed appliance, special care is required not to place the accessories close to the gingival margin, in addition to using light forces porportional to the amount of periodontal attachment, and kept within the biological limits of movement. Correction of the poorly positioned teeth and controlled orthodontic movement can favor remodeling of the alveolar process in all directions. After orthodontic treatment it is important plan containment individually. Integrated orthodontic-periodontal teamwork is essential for reestablishing a healthy periodontium and satisfactory occlusion.